Lithological Control of Stream Chemistry in the Luquillo Mountains, Puerto Rico - Hynek, S. A.; McDowell, W. H.; Bhatt, M. P.; Orlando, J. J.; Brantley, S. L. (Frontiers in Earth Science, 2022)
Meteoric waters move along pathways in the subsurface that differ as a function of lithology because of the effects of chemical and physical weathering. To explore how this affects stream chemistry, we investigated rocks around an igneous intrusion in the Luquillo Mountains (Puerto Rico). We investigated streams on i) unmetamorphosed country rock (volcaniclastic sedimentary strata, VC) surrounding an igneous intrusion, ii) the quartz-diorite intrusion (QD), and iii) the metamorphosed aureole rock (hornfels-facies volcaniclastics, HF). These lithologies differ physically and chemically but weather under the same tropical rain forest conditions. The sedimentary VC lithology is pervasively fractured while the massive QD and HF lithologies are relatively unfractured. However, the QD fractures during weathering to produce spheroidally-weathered corestones surrounded by cm-thick rindlets of increasingly weathered rock. Meteoric waters flow pervasively through the network of already-fractured VC rock and the spheroidally weathered rindlets on the QD, but only access a limited fraction of the HF, explaining why streams draining HF are the most dilute in the mountains. This results in various thicknesses of regolith from thick (VC) to moderate (QD) to thin or nonexistent (HF). The pervasive fractures allow groundwater to flow deeply through the VC and then return to the mainstem river (Río Mameyes) at lower elevations. These “rock waters” drive concentrations of rock-derived solutes (silica, base cations, sulfate, phosphate) higher in the lower reaches of the stream. Water also flows through weathering-induced fractures on the QD at high elevations where rindletted corestones are present in stacks, and this water flux dissolves plagioclase and hornblende and oxidizes biotite. This “rock water” is not generated at lower elevations in the Río Icacos watershed, where stacks of corestones are absent, and contributions to stream solutes derive from weathering of feldspar- and hornblende-depleted saprolite. The stream chemistry in the predominantly QDwatershed (Río Icacos) thus varies from concentrated rock water at channel heads below steep ridgelines toward more diluted “saprolite water” downstream. These observations emphasize the importance of fracture patterns in dictating water flowpaths, stream chemistry, and regolith development in headwater catchments.